Teacher Empowerment Strategies to Bridge Educational Disparities and Enhance School Quality - Dody Alfayed; Shafa Muthiah; Siti Mulkaf Lailawati; Aslamiah Aslamiah; Celia Cinantya (Research, Training and Philanthropy Institution Natural Aceh, 2026)
The disparity in educational quality between urban and rural schools in Indonesia remains a critical obstacle to national development. This study aims to analyze the role of teacher empowerment as a strategic solution to improve school quality amid these inequalities. Using a qualitative literature review, this Research synthesizes academic sources published since 2020 that discuss teacher empowerment and educational quality. The results indicate that empowerment strategies, including continuous professional development, technology-based workshops, and peer collaboration, significantly enhance pedagogical competence, teacher motivation, and student achievement. However, their implementation faces substantial challenges due to uneven teacher distribution and limited infrastructure in frontier, outermost, and disadvantaged (3T) regions. The findings suggest that achieving educational equity requires a systemic shift in which teacher autonomy and capacity building are positioned as core policies rather than supplementary programs. Therefore, policymakers must prioritize investment in human capital in disadvantaged areas to effectively bridge the quality gap and support sustainable national education goals.